Monitoring methods for Diaphorina citri Kuwayama (Hemiptera: Liviidae) on citrus groves with different insecticide application programmes - Miranda, M. P.; dos Santos, F. L.; Bassanezi, R. B.; Montesino, L. H.; Barbosa, J. C. [UNESP]; Sétamou, M. (My University, 2018)
The Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae), is a major citrus pest that transmits the bacteria Candidatus Liberibacter asiaticus and Ca. L. americanus associated with huanglongbing (HLB) disease. Diaphorina citri population densities can affect the effectiveness of its monitoring and sampling methods. Thus, we compared different methods for adult D. citri monitoring in groves with and without insecticide application programmes. Four short-term experiments were carried out, each one lasting four consecutive weeks. In these experiments, sticky cards with different colours (yellow, light green, green and dark green), sweep net, two suction device models, visual inspection and stem tap sampling were assessed. Two long-term experiments were conducted for 4.5 and 5 years, in which only yellow sticky card and visual inspection for D. citri monitoring were assessed. For the short-term experiments, psyllids were detected by all monitoring methods during all sampling periods in areas without chemical control. However, in areas with psyllid control via fortnightly and monthly applications of insecticides, only sticky cards, regardless of their colour, were able to detect the presence of D. citri. Similarly, for the long-term experiments, yellow sticky cards were more effective than visual inspection for detecting and quantifying D. citri in all areas with or without insecticide application. Therefore, in areas where HLB is present and chemical control of psyllid is required, sticky cards are the most reliable option for monitoring D. citri.
Keywords: Asian citrus psyllid; huanglongbing; sticky traps; vector sampling; visual inspection